Ewa Bielska, Andrzej Radziewicz-Winnicki, Adam Roter: Social and educational problems in Poland (Essays and chosen conceptions at the background of the EU accesion). Katowice, WSZ 2005, ss. 119 [recenzja] - Mosiek, Piotr (Chowanna, 2007)
recenzja